Decision Science Can Help Address the Challenges of Long‐Term Planning in the Colorado River Basin. (22nd January 2022) - Smith, Rebecca; Zagona, Edith; Kasprzyk, Joseph; Bonham, Nathan; Alexander, Elliot; Butler, Alan; Prairie, James; Jerla, Carly
Abstract: "Deep uncertainty" is a term that describes planning contexts in which it is impossible to determine the likelihood of any given set of future conditions, there are conflicting performance objectives and priorities, and decision outcomes are unpredictable. Evidence of the relevance of this term in the Colorado River Basin can be found in the unexpected severity and length of the ongoing drought, the existence of a wide range of future streamflow and demand projections and anticipated system requirements, as well as in the diverse range of stakeholders, viewpoints, and priorities that must be considered when developing and analyzing future operating policies. Decision Making under Deep Uncertainty (DMDU) is a branch of decision science devoted to developing planning approaches that can address these challenges. Reclamation began exploring DMDU techniques in 2012 in the Colorado River Basin Water Supply and Demand Study when it used the concepts of adaptation, vulnerability, and robustness in the design and evaluation of portfolios of options and strategies to address a potential supply‐demand imbalance in coming decades. This article presents the basis for continuing to explore DMDU techniques and briefly describes how Reclamation's recent and ongoing DMDU studies could contribute to future planning efforts in the Colorado River Basin.